The Internet in Cyprus 2016 : final report - Stylianou, Stelios; Milioni, Dimitra L. (My University, 2017)
Internet use has been rising steadily in both communities in Cyprus over the last few years. Based on the WIP 2016 survey, it is estimated that more than 70% of the total population aged 15 and over in both communities in Cyprus is using the internet. Internet penetration in the Turkish-Cypriot community has risen more steeply since 2012, slightly surpassing the corresponding figure in the Greek-Cypriot community in 2014 and reaching 76.9% in 2016, more than six percentage units above the corresponding figure in the Greek-Cypriot community (70.8%). Home connections are the most popular in both communities, reaching usage by 97.7% of internet users in the Greek-Cypriot community and by 88.4% in the Turkish-Cypriot community, while mobile data connections are notably more popular in the Turkish-Cypriot community (used by 77.7% of internet users, compared to 61.6% in the Greek-Cypriot community). Greek-Cypriot internet users use computers to connect the internet at a rate of 93.9%, mobile phones at rate of 86.2% and tablets at a rate of 49.1%, compared to 69.0%, 88.9% and 33.1% respectively among Turkish-Cypriot internet users. Mobile phone users in both communities connect to the internet more frequently than users of other devices, with 72.7% reporting doing so several times a day in the Greek-Cypriot community and 62.0% reporting doing so several times a day in the Turkish-Cypriot community.